European airline consolidation - acquisition strategy for a potential takeover of JET2 by Easyjet - Stingel, Hannes (2021)
The group part of the airline industry reportinvestigateswhich airlines are best positioned to operate in a sustainable post-Covid market environment. The results show that low-cost carriers are likely to emerge as the leading business model in the future. The individual part of the airline industry report investigates whether consolidation represents a potential way for easyJet to return to profitability and strengthen its strategic position in a post-pandemic market environment. Analysing a proposed takeover of Jet2 by easyJet provides evidence that easyJet could substantially increase its financial and strategic position on the European airline market after Covid-19.